A framework for analysing blockchain technology adoption: Integrating institutional, market and technical factors. (February 2020) - Janssen, Marijn; Weerakkody, Vishanth; Ismagilova, Elvira; Sivarajah, Uthayasankar; Irani, Zahir
Highlights: Framework for capturing the challenges and issues that organisations face when adopting blockchain technology. A holistic organisational framework integrating Institutional, Market and Technical factors for blockchain adoption. Framework offers companies an initial frame of reference when adopting blockchain applications. Abstract: The adoption of blockchain technologies require the consideration of a broad range of factors, over and above the predominantly technology focus of most current work. Whilst scholarly literature on blockchain technology is only beginning to emerge, majority are focused on the technicalities of the technology and tend to ignore the organizational complexities of adopting the technology. Drawing from a focused review of literature, this paper proposed a conceptual framework for adoption of blockchain technology capturing the complex relationships between institutional, market and technical factors. The framework highlights that varying outcomes are possible, and the change process is focal as this shapes the form blockchain applications take. Factors presented in the framework (institutional, market and technical) interact and mutually influence each other. The proposed framework can be used by organisations as a reference point for adopting blockchain applications and by scholars to expand, refine and evaluate research into blockchain technology.